Syntactic Analysis of Chinese Imperative Function in â€œThe Captainâ€ Movie - Cintiawinata Jung; Julina; Rudiansyah (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
This article analyzes the function of imperative sentences contained in the